Institution building and growth in transition economies - Beck, Thorsten, 1967- 1967- (Policy research working paper, 2005)
"Drawing on the recent literature on economic institutions and the origins of economic development, the authors offer a political economy explanation of why institution building has varied so much across transition economies. They identify dependence on natural resources and the historical experience of these countries during socialism as major determinants of institution building during transition by influencing the political structure and process during the initial years. Their empirical analysis shows that countries that are more reliant on natural resources and spent a longer time under socialist governments are more likely to see former communists remain in power and to start the transition process with less open political systems, with negative repercussions for the development of market-compatible institutions. Using natural resource reliance and the years under socialism to extract the exogenous component of institution building, the authors also show the importance of institutions in explaining the variation in economic development and growth across transition economies during the first decade of transition. "--World Bank web site